1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Tangent will not meet the curve again

  1. May 2, 2014 #1
    1. The problem statement, all variables and given/known data

    can anyone give me hint on how to show the tangent will not meet the curve again?

    2. Relevant equations

    3. The attempt at a solution

    Attached Files:

  2. jcsd
  3. May 2, 2014 #2


    User Avatar
    2017 Award

    Staff: Mentor

    Just plug your coordinates in the equation for the tangent and look for all solutions?
  4. May 2, 2014 #3

    Ray Vickson

    User Avatar
    Science Advisor
    Homework Helper

    You can try to check the convexity (or concavity) properties of the curve ##y = Y(x)##, by checking the second derivative ##d^2 y / dx^2##.
  5. May 5, 2014 #4
    what's the relationship between checking the concavity and show the curve will not meet the tangent again?
  6. May 6, 2014 #5


    User Avatar
    Homework Helper

    Have you tried sketching the curve?
  7. May 6, 2014 #6

    Ray Vickson

    User Avatar
    Science Advisor
    Homework Helper

    Google "convex function" or "concave function". See, eg., http://ece.tamu.edu/~cui/ECEN629/lecture2.pdf [Broken] slide 4.
    Last edited by a moderator: May 6, 2017
  8. May 6, 2014 #7


    User Avatar
    Science Advisor

    It might be simplest to eliminate the parameter and write a Cartesian equation for this curve:
    [itex]x= ln(cos(\theta)[/itex] so [itex]e^x= cos(\theta)[/itex] and [itex]y= ln(sin(\theta)[/itex] so [itex]e^y= sin(\theta)[/itex]. Then [itex]e^{2x}+ e^{2y}= cos^2(\theta)+ sin^2(\theta)= 1[/itex]. Of course, for [itex]0< \theta< \pi/2[/itex], [itex]cos(\theta)[/itex] goes from 1 to 0 so x goes from 0 to [itex]-\infty[/itex] and y goes from [itex]-\infty[/itex] to 0. The graph is in the third quadrant.

    At [itex]\theta= \pi/4[/itex], [itex]y= x= -(1/2)ln(2)[/itex] so that [itex]e^{2y}= e^{2x}= 2^{-1/2}= 1/2[/itex]. Further, differentiating [itex]e^{2x}+ e^{2y}= 1[/itex], [itex]2e^{2x}+ 2e^{2y}y'= 0[/itex] so, at [itex](1/2, 1/2)[/itex], [itex]y'= -1[/itex]. The tangent line is [itex]y= -1(x+ (1/2)ln(2))- (1/2)ln(2)= -x- ln(2)[/itex] and the question becomes solving [itex]e^{2x}+ e^{2(-x- ln(2)}= e^{2x}- (1/2)e^{-2x}= 1[/itex].
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted